Pengaruh Lingkungan Kerja dan Motivasi Terhadap Kepuasan Kerja Karyawan di Pabrik Gula Gempolkrep Mojokerto - Mu’arif Alif Usman (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
The research purpose is to know of work environment and motivation on employee job satisfaction in sugar company of gempolkrep mojokerto. This kind of research used technik data analysis qualitatif with approach associative analysis. This Populasi taken was 296 permanent employees, take of sample by random sampling, this sample in this research amount 170 respondent, this research used technik with the collection the survey data or observasi, interview and documentation. Analyze data using statistical methods using validity and reliability, classic assumption tests, and hypothesis testing with multiple linear regression formulas. The results showed that, (1) The work environment had a positive and significant effect on job satisfaction, (2) Motivation has a positive and significant effect on job satisfaction, and (3) Simultaneous work environment and motivation influence the work satisfaction of Gempolkrep sugar factory employees.